AHMAD BIN HANBAL (PEMIKIRAN FIKIH DAN USHUL FIKIHNYA) - Marzuki Marzuki (State Institute of Islamic Studies (IAIN) Palu, 2005)
Ahmad bin Hanbal is popular not only as a faqih but also as a muhaddith. His authority on istimbath can be seen from his method of istimbath. He places the Qur’an and hadith as the main sources of law in his istimbath. In addition, he employs companions’ fatwa agreed upon by them. The reason for this is that companions are undoubtedly credible persons. Other sources of law he uses in his istimbath are hadith mursal and hadith dha’if, that is hadith of no tsiqah in some of its narrators. He also employs such methods of istimbath as qiyas, ijma’, al-mashalih al-mursalah, istihsan, sad al-zari’ah, and istihsab.Kata kunci : Ahmad bin Hanbal, fikih, ushul fikih